2015
DOI: 10.18272/aci.v7i2.271
|View full text |Cite
|
Sign up to set email alerts
|

Determinación de elementos mayores en sedimentos provenientes de zonas afectadas por actividades petroleras en Ecuador

Abstract: * g −1 . Mientras que las concentraciones en el bulk de los sedimentos fueron , Na: 3-24 y Mn: 0.43-1.28 mg g −1 . En las muestras analizadas, el 43 % del Na, el 93 % del Fe, el 70 % de Mg, el 62 % de Mn y el 94 % de K están asociados con la fracción fina de los sedimentos. Las concentraciones de Mg, Na y Mn están influenciadas por las actividades petroleras mientras que el contenido de Fe, K y Al está relacionado con el origen natural de los sedimentos. Sin embargo, aguas abajo, hasta la frontera con Perú, no… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
9
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
3

Relationship

2
1

Authors

Journals

citations
Cited by 3 publications
(10 citation statements)
references
References 40 publications
1
9
0
Order By: Relevance
“…Conductivity values ranged from 19.87 μS/cm in the Caoní River to 616.00 μS/cm in the Monjas River. According to the US Environment Protection Agency (EPA), the suggested range of conductivity for surface waters is 150–500 μS/cm, meaning that the obtained values in this study are lower and higher than the suggested ones [ 19 ]. Half of the analyzed rivers evidenced conductivity values lower than the minimum value (150 μS/cm), more exactly, the Caoní, Mashpi, Pachijal, Chiche, Blanco, Alambi, Pilatón, Mindo and Guachalá Rivers.…”
Section: Resultsmentioning
confidence: 85%
See 2 more Smart Citations
“…Conductivity values ranged from 19.87 μS/cm in the Caoní River to 616.00 μS/cm in the Monjas River. According to the US Environment Protection Agency (EPA), the suggested range of conductivity for surface waters is 150–500 μS/cm, meaning that the obtained values in this study are lower and higher than the suggested ones [ 19 ]. Half of the analyzed rivers evidenced conductivity values lower than the minimum value (150 μS/cm), more exactly, the Caoní, Mashpi, Pachijal, Chiche, Blanco, Alambi, Pilatón, Mindo and Guachalá Rivers.…”
Section: Resultsmentioning
confidence: 85%
“…Although the contamination of Pichincha’s rivers is visible nowadays, few studies have been published regarding their microbial and chemical quality [ 19 , 20 , 21 ]. The last study conducted by the municipal water service of Quito (EPMAPS) revealed that most of the rivers in the south part of the capital exceeded the authorized microbial limits of potable water by 3000% [ 22 ].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…High values of conductivity were found in Guayas (4137.33 µS cm −1 ), Esmeraldas (938.53 μS cm −1 ), and Machángara (501.10 µS cm −1 ) Rivers. The Environmental Protection Agency (EPA) suggests a range of conductivity between 150 and 500 μS cm −1 , and therefore the conductivity values found in the river basins are higher than the recommended values 18 . In addition, the ORP values found in this study were between 62.44 and 412.77 mV, in which Coca River showed the highest value of ORP.…”
Section: Resultsmentioning
confidence: 94%
“…These contaminants cause variations of the physicochemical properties of water resources, which directly influence microbial proliferation, and therefore physicochemical analysis is also an indispensable feature for the water quality assessment. Finally, high levels of heavy metals (such as Pb, Cr, Cu, and Zn) represent a serious public health risk because they are not biodegradable 18 .…”
Section: Introductionmentioning
confidence: 99%